The Effect of Metal Fibres and Borax Powders on the Wear and Friction Performances of the Organic Based Brake Pads - İrem Burcu Algan; Adem Kurt (Металлофизика и новейшие технологии, 2017)
The use of various materials in brake pad compositions is widely studied. In this study, the borax powders or the copper or bronze fibres are added in non-asbestos organic brake pad composition to examine the effects of type and quantity of additive on the friction and wear characteristics of brake pads. Firstly, three different specimen groups are developed by powder metallurgy method, which contain various amounts (1.5, 3, 4.5 and 6% weight) of borax powder, copper fibre, and bronze fibre.